2004
DOI: 10.1002/pse.164
|View full text |Cite
|
Sign up to set email alerts
|

US–Japan cooperative earthquake research program on CFT structures: achievements on the Japanese side

Abstract: The US–Japan Cooperative Earthquake Research Program began in 1979, following the recommendations as outlined in the final report of the US–Japan Planning Group for the Program. The first four phases of the Program have been implemented on: (1) reinforced concrete; (2) structural steel; (3) masonry, and (4) precast/prestressed concrete. Phase 5, on composite and hybrid structures, was carried out from the fiscal year 1993 over 5‐years. In this phase, the following four research topics were executed: (1) new ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Research works on concrete-filled steel tubes conducted by Schneider [5] showed that compared to square and rectangular columns, circular ones offer substantial postyield strength and stiffness. In the last few decades, experimental, numerical and analytical investigations have been carried out on the structural behaviour of concrete-filled steel circular columns under various loading conditions, as summarized in literature [6][7][8][9][10][11]. Commonly, there are two methods for increasing the resistance of concrete-filled steel columns [1].…”
Section: Introductionmentioning
confidence: 99%
“…Research works on concrete-filled steel tubes conducted by Schneider [5] showed that compared to square and rectangular columns, circular ones offer substantial postyield strength and stiffness. In the last few decades, experimental, numerical and analytical investigations have been carried out on the structural behaviour of concrete-filled steel circular columns under various loading conditions, as summarized in literature [6][7][8][9][10][11]. Commonly, there are two methods for increasing the resistance of concrete-filled steel columns [1].…”
Section: Introductionmentioning
confidence: 99%
“…The second group includes the phenomenological calculation methods based on experimental data and able to take into account all advantages of CFST [13,14].…”
Section: Actual Problems Of Engineering Mechanicsmentioning
confidence: 99%
“…Due to a large percentage of inelastic damage occurring in the beam elements, existing seismic standard codes require a strong-column weak-beam mechanism during their design [ 13 , 14 , 15 ]. A better understanding of the bending behavior of these elements and an appropriate method of modeling this behavior is required before steel tubes can be used for seismic design applications [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%